University Canteen Business Process Improvement to Increase Sustainability - Christina Wirawan (Universitas Kristen Maranatha, 2019)
As information, science and technology developed and also a quick change of the business environment, the service sector developed and became an important sector that gives significant value added. Because of service sector strategic role, there's a need for developing strategies that aim to increase service's performance and sustainability. A university canteen in a private university is one of service business that runs by business unit and has to raise their performance to survive and sustain in a competitive environment. The number of customers that buy food in the canteen is only about 5% of all students, lecturers and employees in the university, means there are still many potentials. From survey and observation, easily, quickly, give comfort place and have a low price is the crucial expectation of customer that attract them to buy. This paper will provide suggestion so that the canteen can provide service that meets customer's expectation, based on procedure simplification that shortened the time, eliminate and reduce cost by increasing customer's role. For some extent, to raise canteen's profit and capacity utilization, delivery service with the business unit as a platform to enable co-creation, also suggested